Respostas

2014-02-11T16:54:55-02:00
48 - (15 - x) - x (18 - x) =
48 - 15 + x - 18x + x² = 0
x² - 17x + 33 = 0
a = 1                      b = - 17             c = 33

Δ = b² - 4 . a . c
Δ = (- 17)² - 4 .1 . 33
Δ = 289 - 132
Δ = 157

x = - b ± √Δ
     -------------
        2 . a
x = - (- 17) ± √157
     -----------------------
               2 . 1
x = 17 ± 12,53
     ------------------
            2 
x' = 17 + 12,53 
            2
x' = 29,53 ÷ 2
x' = 14,765

x" = 17 - 12,53 
            2
x" = 4,47 ÷ 2
x" = 2,235

Resposta: {14,765; 2,235}